Plasma parameters estimation in the non-self-sustained gas discharge with hollow anode - Misiruk, I.O.; Tymoshenko, O.I.; Taran, V.S. (Вопросы атомной науки и техники, 2018)
A simple global model was built for estimation of the plasma properties in the non-self-sustained gas discharge with
hollow anode [2, 4]. The calculated results are compared with experimental data of probe measurements. The applicability
and limitations of the model are discussed. Побудована проста глобальна модель для оцінки параметрів плазми в несамостійному газовому розряді з
порожнистим анодом. Результати обчислень порівнюються з даними зондових вимірювань. Обговорюються
застосовність та обмеження розглянутої моделі. Построена простая глобальная модель для оценки параметров плазмы в несамостоятельном газовом разряде с полым анодом. Результаты вычислений сравниваются с данными зондовых измерений. Обсуждается применимость и ограничения рассмотренной модели.